Identifikasi Cemaran Bakteri Coliform dan Escherichia coli Pada Jamu Gendong Dengan Metode Most Probable Number (MPN) di Karawang Timur - Rivandia Listi; Ahsanal Kasasiah; Lely Sulfiani Saula (Indobiosains, 2022)
In Indonesia, herbal medicine is still very popular, especially ginger and curcurma herbs. Both herbs are believed to increase the body's immunity for those who consume them. Processing of herbal medicine which is still carried out with simple process and tools is very possible for contamination by microbes. Coliform bacteria and Escherichia coli are used as indicators of contamination because the habitat of these two bacteria is the digestive tract or in the rest of the feces. These bacteria can cause mild to serious digestive disease. Therefore, it is necessary to conduct this research with the aim of detecting the presence of Coliform and Escherichia coli bacteria and to determine the concentration of these two bacteria in the ginger and curcuma herbs. The research method used is the Most Probable Number (MPN) using 4 samples of herbal medicine with two repetitions. The results showed that Coliform and Escherichia coli contamination were found in all samples. Concentrations Coliform in ginger herbs ranging from 4-2400 MPN/ml while for Escherichia coli it ranged from 4-210 MPN/ml. In Curcuma herbs the Coliform concentration ranges from 21-28 MPN/ml while the value for Escherichia coli ranges from 4-21 MPN/ml. Keywords: MPN, Coliform, Escherichia coli, ginger, curcuma